Proyección de Picasso en la obra del poeta Paul Eluard: una relación entre Yeux fértiles - Gómez Ángel, Brisa (Anales de Filología Francesa, 2009)
Picasso’s work inspired a substantial part of Eluard’s poetics, strongly influenced by the representations of the painter. The confrontation that followed when these two men met was reflected by Eluard in his work Physique de la poésie: “A partir de Picasso, les murs s’écroulent. Le peintre ne renonce pas plus à sa réalité qu’à la réalité du monde. Il est devant un poème comme le poète devant un tableau. Il rêve, il imagine, il crée.” (Eluard 1968: 938) Thus, the expression of a mutual recognition between the two artistic worlds is made evident through the Eluardian verses concerning Picasso, a relationship that became apparent in a collection of poems by Paul Eluard published in 1936: Les yeux fertiles. This paper aims at unravelling the poetic discourse of the fraternity between creators, the recognition between the forms of expression of their representations and their vision of the world.